Implementasi Fuzzy Inference System (FIS) Menggunakan Metode Mamdani Dalam Menentukan Tingkat Kepuasan Siswa Terhadap Penggunaan Sarana Dan Prasarana Pendidikan Berbasis Web (Studi Kasus : SMP Islam Al-Falaah Ciputat) - Fikri, Muhammad; Zakaria, Hadi (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Al-Falaah Islamic Middle School is an educational institution at the junior high school (SMP) level, established in 2009 and has a vision to produce the next generation of people who believe and fear Allah SWT. Al-Falaah Islamic Middle School has a problem with facilities and infrastructure, namely where there are still many weaknesses in receiving this service, so that it has not been able to meet the quality expected by students and parents. Therefore, in solving this problem, a decision support system was created to manage service strategies in facilities and infrastructure using the Mamdani Fuzzy Inference System method. The author conducted research by selecting the best criteria for service quality so as to improve the quality of school facilities and infrastructure. In this writing the author uses the programming language HTML, PHP, and MySQL Database to store data. From the results of this study it is hoped that the application of determining the level of satisfaction with the mamdani method can make evaluations for schools in improving the quality of facilities and infrastructure for schools so that they continue to be trusted by the community and prospective parents of students.